The Correlation Between Self Confidence and Speaking Ability of the Tenth Grade Students’ of SMAN 3 Enrekang - Arya Priyangga Sumardi; Syarifuddin Dollah; Syarifah Farahdiba (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
The purpose of this study is to ascertain whether those two factors significantly correlate with one another. With a total of 315 students in the tenth grade at SMAN 3 Enrekang, the population of this study was composed of 32 of those students. Purposive sampling was used to choose the sample. This study uses a quantitative correlational research design. The Sirchi (2021) questionnaire was used to obtain the data on self-confidence, while the monologue exam was used to collect data on speaking skills. The SPSS 25 program was used to analyze the data for this study. The study's findings suggest that there is a strong relationship between students' self-confidence and speaking ability because the correlation analysis between the two variables indicated a significant value (0.00) and a Pearson correlation (+0.55). The conclusion of this study is that students should be encouraged to pay more attention to their self-confidence because it can impact their ability to talk.